Effects of Selective Serotonin Reuptake Inhibitors on Auditory Processing: Case Study - Gopal, Kamakshi V.; Daly, D. Michael; Daniloff, Raymond G.; Pennartz, Lori (Journal of the American Academy of Audiology, 2000)
Auditory sensitivity and processing ability were evaluated in a patient who suffered from hyperacusis, difficulty understanding speech, withdrawn depression, lethargy, and hypersensitivity to touch, pressure, and light. Treatment with fluvoxamine and fluoxetine (selective serotonin reuptake inhibitors) reversibly alleviated complaints. Testing while medicated and unmedicated (after voluntary withdrawal from medication for several weeks) revealed no difference in pure-tone thresholds, speech thresholds, word recognition scores, tympanograms, or acoustic reflex thresholds. Medicated SCAN ● A (a screening test for central auditory processing disorders) results were normal, and unmedicated results were abnormal. Unmedicated transient otoacoustic emissions and auditory brainstem response waves I, III, and V were significantly larger bilaterally. Uncomfortable loudness levels indicated greater tolerance during the medicated condition. Central processing and vigilance were evaluated with analog-synthesized three-formant consonant-vowel syllables. While medicated, responses to stimuli at each ear revealed well-defined, labeling crossovers of about 90 msec. Vowel identification matched normal subject responses; labeling of /gE/jE/ and /bE/wE/ continua was well defined but all crossover points differed from normals (p < .0001). During unmedicated testing, responses to /gE/jE/ began at medicated levels but approached chance levels for the entire continuum within 10 min; labeling of /bE/wE/ was consistent with medicated responses throughout with earlier than normal crossover points.Abbreviations: ABRs = auditory brainstem responses, ALRs = auditory late potentials, CNS = central nervous system, GABA = gamma-aminobutyric acid, 5–HT = 5–hydroxytryptamine, OCB = olivocochlear bundle, SAS = sparse acoustic stimuli, SSRIs = selective serotonin reuptake inhibitors, TEOAEs = transient evoked otoacoustic emissions, UCL = uncomfortable loudness level
Keywords: Auditory brainstem responses; central auditory processing; depression; hyperacusis; phoneme identification; selective serotonin reuptake inhibitors; serotonin